Acute Myopic Shift after a Single Dose of Acetazolamide: A Case Report and Review of the Literature - Kaisari, Eirini; Abouzeid, Hana; Magnin, Laurent; Boeuf, Melanie; Gkaragkani, Evangelia; Schalenbourg, Ann; Wolfensberger, Thomas J.; Kaeser, Pierre-François (Klinische Monatsblätter für Augenheilkunde, 2024)
We report the case of a 32-year-old male who presented with an acute myopic shift as a result of uveal effusion following a single administration of 250 mg acetazolamide. The drug was discontinued and following cycloplegia and topical steroid therapy, we observed progressive deepening of the anterior chamber, reopening of the iridocorneal angle, and complete resolution of the myopic shift after 5 days. A literature review since 1956 identified 23 cases, including ours, which developed a myopic shift after a median time of 24 h (3 – 24) following a median dose of 500 mg (125 – 1000) acetazolamide, with about a third complicated by angle closure ocular hypertension. This presumed idiosyncratic reaction can occur without prior drug exposure and independent of the phakic status. Treatment options include systematic drug withdrawal associated with cycloplegia, anti-glaucomatous agents, and/or corticosteroids. Full recovery is achieved within about 5 days (2 – 14). Given the widespread use of acetazolamide, awareness of this idiosyncratic reaction is crucial to avoid complications of acute angle-closure glaucoma.
Keywords: acetazolamide; uveal effusion; angle closure; myopic shift; idiosyncratic drug reaction; UBM